Postcolonial Subjects : Francophone Women Writers. - Green, Mary Jean (University of Minnesota Press, 1996)
This groundbreaking volume highlights the work of contemporary women writing in French whose cultural links, ethnic identities, and historical roots lie outside France. The writings of these women emanate from the cultures of Africa and the Indian Ocean, the Middle East, the Caribbean, Southeast Asia, and Quebec and other French-speaking regions of Canada.